Evaluation of Risk Culture Implementation at PT XYZ Financing Company - Nico Priyantha Tarigan; Tubagus Muhamad Yusuf Khudri (E-Jurnal Akuntansi, 2025)
This research evaluates the implementation of risk culture at PT XYZ, focusing on the IRM Framework 2012. Despite its significance, PT XYZ's risk culture remains suboptimal, primarily due to low employee risk awareness. This has led to a three-year surge in the Allowance for Doubtful Accounts, potentially impacting profitability. A mixed method study combining surveys and interviews, was conducted to investigate underlying causes. Results reveal an "adventurous" decision-making style among employees, which while fostering innovation, can lead to impulsive choices. Furthermore, the analysis of eight risk culture aspects identified four areas for improvement: Responding to Bad News by encouraging open communication and recognizing risk reporting, Rewarding Appropriate Risk Taking by aligning incentives with responsible risk-taking behaviors, Risk Resources by strengthening the risk management department's independence and capacity and Risk Competence by enhancing employee risk knowledge and skills through training and certification.By addressing these areas, PT XYZ can bolster its risk culture and mitigate potential future losses.